On Broadway : art and commerce on the great white way - Adler, Steven, 1953- (Southern Illinois University Press, 2004)
At a critical, transitional moment in the history of Broadway and, by extension, of American theatre itself former Broadway stage manager Steven Adler enlists insider perspectives from sixty-six practitioners and artists to chronicle the recent past and glimpse the near future of the Great White Way. From marquee names to behind-the-scenes power brokers, Adler has assembled a distinctly knowledgeable cast of theatre's elite, including Stephen Sondheim, Arthur Laurents, Des McAnuff, Frank Rich, Robin Wagner, Rocco Landesman, Robert Longbottom, Todd Haimes, Bernard Gersten, and Alan Eisenberg.On Broadway: Art and Commerce on the Great White Way spotlights the differing vantage points of performers, artists, writers, managers, producers, critics, lawyers, theatre owners, union leaders, city planners, and other influential players. Each details his or her firsthand account of the creative and economic forces that have wrought extraordinary changes in the way Broadway theatre is conceived, produced, marketed, and executed. Once the paramount site of American theatre, Broadway today is becoming a tourist-driven, family-friendly, middle-class entertainment oasis in Midtown, an enterprise inextricably bound to the larger mosaic of national and international professional theatre.